A better way to carry out collaborative research. Issue 1 (January 2022) - Kent, Samuel; Dawoud, Basim; Henry, Alasdair; Blore, Chris; Jeffries, Chris; Kumar, Dee; Geddes, Alan
Abstract : Introduction: Collaborative research creates larger datasets with more power and impact. Yet conducting collaborative research can be complex. Over the past five years the Maxillofacial surgery Trainees Research Collaborative (MTReC) has engaged with over 50 OMFS units and over 100 individual OMFS trainees to publish ten peer reviewed journal articles and around 25 oral and poster presentations. We aim to share our learnings to encourage involvement with, and leadership of future collaborative research within OMFS. Methods: 1) Determining appropriate research questions and timescales 2) Answering questions over ownership of data and setting up appropriate tools to gather data 3) Motivating and engaging with trainees 4) Appropriate citation and authorship. Results: Collaborative research is suited to answering research questions which require more data than a single researcher could gather. By sharing the work required, greater volumes of data and hence greater statistical power is available. Carrying out projects with timescales contingent on job rotations allows trainees to be involved throughout a project, and avoids loss of data and collaborators. Clear communication with collaborators is key, and incentivisation to collect data is important. Trainees are often motivated to carry out research, and have time to do so. Authorship varies between journals, and requires some negotiation to ensure correct citation. Conclusions: Collaboration has huge potential to enhance engagement with, and quality of research within OMFS.